2013
DOI: 10.1111/ppa.12143
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Botrytis in New Zealand vineyards and the significance of its seasonal and regional variation

Abstract: Species-and population-specific differences in fungicide resistance and aggressiveness within Botrytis makes basic data on genetic diversity important for understanding disease caused by this fungus. Genetic diversity of Botrytis was surveyed between 2008 and 2012 from grapes from five New Zealand wine-growing regions. A total of 1226 isolates were gathered from symptomless flower buds at the start of the growing season and 1331 isolates from diseased fruit at harvest. Two species were found, B. cinerea and B.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 19 publications
(96 reference statements)
3
34
1
Order By: Relevance
“…In French and New Zealand vineyards, B. pseudocinerea has been found more frequently on vegetative tissues and flowers than on mature grapes. This was attributed to a higher saprotrophic competitiveness and preferred colonization of flowers but lower virulence on the berries than that of B. cinerea (12,13,17). Our data only partly support these conclusions.…”
Section: Discussioncontrasting
confidence: 50%
See 4 more Smart Citations
“…In French and New Zealand vineyards, B. pseudocinerea has been found more frequently on vegetative tissues and flowers than on mature grapes. This was attributed to a higher saprotrophic competitiveness and preferred colonization of flowers but lower virulence on the berries than that of B. cinerea (12,13,17). Our data only partly support these conclusions.…”
Section: Discussioncontrasting
confidence: 50%
“…In agreement with an earlier report (23), we confirmed that B. pseudocinerea strains were Ͼ20-fold more sensitive than B. cinerea to fenpropidin, except for the fenhexamid-sensitive group B strain. In New Zealand, B. pseudocinerea strains preselected for fenhexamid resistance belonged to group A and group B, showing that group B isolates can have the HydR1 phenotype (17). We have optimized discriminatory growth tests on agar medium containing fenhexamid and fenpropidin as a convenient preliminary tool to distinguish between B. pseudocinerea and B. cinerea strains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations